2011
DOI: 10.1364/oe.19.000687
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity, broadband stimulated-Brillouin-scattering-based slow light using fast noise modulation

Abstract: We demonstrate a 5-GHz-broadband tunable slow-light device based on stimulated Brillouin scattering in a standard highly-nonlinear optical fiber pumped by a noise-current-modulated laser beam. The noisemodulation waveform uses an optimized pseudo-random distribution of the laser drive voltage to obtain an optimal flat-topped gain profile, which minimizes the pulse distortion and maximizes pulse delay for a given pump power. In comparison with a previous slow-modulation method, eye-diagram and signal-to-noise r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The noise contribution from amplitude jitter (σ 2 aj ), which is due to the pattern dependence of the SBS slow-light effect, has a steeper slope than the other noise sources and becomes the dominant noise source for P p > 350 mW. In light of the fact that the slow-light delay increases linearly with P p , our results show that it is essential to minimize the pattern dependence in high-delay systems, which is enabled using a flattop gain profile, for example [20,26].…”
Section: System Noise Analysismentioning
confidence: 78%
See 3 more Smart Citations
“…The noise contribution from amplitude jitter (σ 2 aj ), which is due to the pattern dependence of the SBS slow-light effect, has a steeper slope than the other noise sources and becomes the dominant noise source for P p > 350 mW. In light of the fact that the slow-light delay increases linearly with P p , our results show that it is essential to minimize the pattern dependence in high-delay systems, which is enabled using a flattop gain profile, for example [20,26].…”
Section: System Noise Analysismentioning
confidence: 78%
“…It is also possible to simultaneously tailor the shape of the broadened resonance to minimize pulse distortion [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It has been shown that a flattop SBS gain profile minimizes distortion and increases the slow-light delay [19][20][21]26]. In our experiments described below, we generate a nearly ideal flattop SBS gain profile with a spectral width (full-width at half-maximum) ΔΩ G =2π ¼ 5 GHz by broadening the spectrum of the pump laser (see Fig.…”
Section: A Stimulated Brillouin Scatteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the delay time with error-free operation (BER<10 −9 ) is only 83.0 ps. With a 20-dBm Brillouin pump, the BER decreases and then increases with received optical power, which may be mainly attributed to the serious Brillouin ASE noises at higher pump power [18,19] . The eye diagrams of signals with the different pump powers and their corresponding delay times are shown in Fig.…”
mentioning
confidence: 99%